Pengolahan Air Laut Menggunakan Generator Uap Untuk Menghasilkan Air tawar - Jefri Lianda; Dadang Enda; Ariadi Ariadi; Suhaimi Suhaimi; Wira M (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
The need forfresh waterandcleanis always top priorityin human life. Not least for the people who live around the coast. Small Siak district community and Bukit Batu Bengkalis get clean water tasted salty. This research will be to process sea water into fresh water potable through steam generator. This process utilizes thermal energy to evaporate salt water. The water vaporis then cool edin to water drop let sand collected as are sult of fresh clean water. The clean water produced from the distillation process has a very good level of health when compared with water that comes from processing using chemicals. The quality of water produced by 22ppm (parts per million) using a TDS meter.Keywords: ppm, sea water, steam generators , tds